Discovery of a new species of the genus Planaeschna from Northern Vietnam, with a first description of male P. tomokunii - Sasamoto, Akihiko; Do, Cuong; Van, Lien Vu (Zootaxa, 2013)
A new species of Planaeschna McLachlan, P. guentherpetersi sp. nov. (holotype male and paratype female) from Phu Tho province, northern Vietnam, is described and illustrated. In addition, the male of P. tomokuniiAsahina, 1996, which was known from only the holotype female, is described for the first time, based on newly collected material of both sexes, from the type locality, Tam Dao, Vinh Phuc province, northern